Gambaran Pelaksanaan Hand Hygiene Keluarga dengan Neonatus dan Bayi yang dirawat di Rumah Sakit - Oktavia, Dina; Erwin, Erwin; Muthia Zukhra, Ririn (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Introduction: The implementation of hand hygiene for the patient's accompanying family in the hospital is important to pay attention to the emergence of HALs, one of the prevention efforts is hand hygiene. This study aimed to determine the description of the implementation of family hand hygiene with hospitalized neonates and babies. The study took place at Arifin Achmad General Hospital, Pekanbaru Method: this study was a descriptive study with a sample of 59 respondents with total sampling techniques. the collecting data was using by observarion and questionnaires. Data analysis using descriptive tests. Results: the majority of respondents used hand wash media as much as 55 (93.2%) and hand rub media as much as 4 (6.8%). The majority of respondents' hand wash implementation techniques were classified as imperfect category, namely 55 people (91.7%). The majority of respondents did hand hygiene in the first moment with a good category of 35 (59.3%), the fourth moment with a good category of 35 (59.3%) and the fifth moment with a good category of 31 (52.5%). Conclusion: it is recommended that hospitals continue to provide information about hand hygiene.